Joseph Fouque (1755-1819) rentoileur de tableaux au Musée du Louvre - Aude Briau (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The opening of the musée du Louvre at the end of the 18th century allowed a great interest for painting restoration,due to the seizure of artworks all across Europe by the French revolutionaries and then by Napoleon's army. Among the specialists of the new institution, Joseph Fouque (1755-1819) took a great part in support’s restoration. Such a biographical approach can help considering the restoration methods at that time.